Determination of triazine herbicides and their metabolites in multiple medicinal parts of traditional Chinese medicines using streamlined pretreatment and UFLC-ESI-MS/MS. (January 2018) - Liu, Congmin; Dou, Xiaowen; Zhang, Lei; Li, Qian; Qin, Jia'an; Duan, Yaping; Yang, Meihua
Abstract: A rapid, sensitive, and reliable ultra-fast liquid chromatography combined with electrospray ionization tandem mass spectrometry (UFLC-ESI-MS/MS) method was established and applied to simultaneous determination of 31 triazine herbicides and their metabolites in multiple medicinal parts of traditional Chinese medicines (TCMs). A streamlined pretreatment approach using one-step extraction and dilution was proposed, which provided high-throughput processing, excellent recovery, and negligible interference. Afterwards, multiple-reaction monitoring (MRM) and information-dependent acquisition (IDA) triggered enhanced product ion spectra (EPI) was adopted to identify and quantify the targets in a single analysis. The optimized method was then validated according to the guidelines of the European Commission for the following parameters: Matrix effects, specificity, accuracy, precision, linearity, range, and stability. The LOD and LOQ for the 31 triazine herbicides were 0.1–10 μg kg −1 and 0.5–25 μg kg −1, respectively. Recoveries at three concentration levels were within 67.9–120.3% with an associated precision RSD <20%. Using the proposed approach, trazines herbicides were determined from 44 commercially available TCMs. The detection rate of triazine herbicides residues was 15.9% of the total samples. Among them, atrazine, simeton, and simetryn were found in the radix, herba, and seed TCMs with values far below the referenced maximum residue limits (MRLs), but no residues were detected in either the flos or fructus. Taken together, this method has the potential to provide a means for triazines screening in extensive matrices, thereby laying the foundation for pesticide registration on TCMs. Moreover, it has the potential to guide further triazine residue control in TCMs. Graphical abstract: Image 1 Highlights: A sensitive and reliable UFLC-ESI-MS/MS method was developed to identify and quantify 31 triazines in a single run. Triazine residues were screened for in multiple medicinal parts of TCMs, including radix, flos, herba, fructus, and seed. A rapid and streamlined pretreatment using one-step extraction and dilution was proposed. Triazine herbicides were found in radix, herba, and seed TCMs, but no residues were detected in either the flos or fructus.